Directional actin polymerization associated with spotted fever group Rickettsia infection of Vero cells. - Heinzen, R A (1993)
Members of the spotted fever group (SFG) of rickettsiae spread rapidly from cell to cell by an unknown mechanism(s). Staining of Rickettsia rickettsii-infected Vero cells with rhodamine phalloidin demonstrated unique actin filaments associated with one pole of intracellular rickettsiae. F-actin tails greater than 70 microns in length were seen extending from rickettsiae. Treatment of infected cells with chloramphenicol eliminated rickettsia-associated F-actin tails, suggesting that de novo protein synthesis of one or more rickettsial proteins is required for tail formation. Rickettsiae were coated with F-actin as early as 15 min postinfection, and tail formation was detected by 30 min. A survey of virulent and avirulent species within the SFG rickettsiae demonstrated that all formed actin tails. Typhus group rickettsiae, which do not spread directly from cell to cell, lacked F-actin tails entirely or exhibited only very short tails. Transmission electron microscopy demonstrated fibrillar material in close association with R. rickettsii but not Rickettsia prowazekii. Biochemical evidence that actin polymerization plays a role in movement was provided by showing that transit of R. rickettsii from infected cells into the cell culture medium was inhibited by treatment of host cells with cytochalasin D. These data suggest that the cell-to-cell transmission of SFG rickettsiae may be aided by induction of actin polymerization in a fashion similar to that described for Shigella flexneri and Listeria monocytogenes.